2020
DOI: 10.17582/journal.vsrr/2020.6.2.132.137
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Major Pathogens Associated with Clinical and Subclinical Mastitis in Dairy Camel (Camelus dromedarius) in Benadir Region of Somalia

Abstract: A cross-sectional study of camel mastitis was conducted on 150 lactating camels from July to December 2019 to figure out the prevalence of both clinical and subclinical mastitis in lactating camels in the Benadir Region of Somalia and also to recognize the associated microorganisms as causal agents of mastitis. The prevalence of this study was measured by using California mastitis test (CMT). Milk samples were collected from the Deyniile District, Benadir Region of Somalia. The overall prevalence of mastitis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
3
5
0
Order By: Relevance
“…The prevalence of subclinical mastitis in she camels in this study (10.6%) aligns with previous studies by Mohamud et al ( 8 ) who reported 9.8% in Somalia, and Juboori et al ( 22 ) who reported 11.67% in the UAE. Similarly, the findings are comparable to Balemi et al ( 10 ) who reported 14.5% in Ethiopia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of subclinical mastitis in she camels in this study (10.6%) aligns with previous studies by Mohamud et al ( 8 ) who reported 9.8% in Somalia, and Juboori et al ( 22 ) who reported 11.67% in the UAE. Similarly, the findings are comparable to Balemi et al ( 10 ) who reported 14.5% in Ethiopia.…”
Section: Discussionsupporting
confidence: 92%
“…Reports of sub-clinical mastitis in camels have been documented in various regions of Africa, including Egypt ( 7 ), Somalia ( 8 ), and Kenya ( 9 ). Very recent studies conducted in two pastoral districts in southern Ethiopia, reported a prevalence of sub-clinical mastitis in dairy cows, camels, and goats as 33.3, 26.3, and 25.0%, respectively; and quarter-level prevalence of sub-clinical mastitis in cows, camels and goats as 17.6, 14.5, and 20%, respectively ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, occurrence of mastitis among lactating camel has been reported from different camel rearing countries like Somalia [14], Sudan [15], Kenya [16], Israel [17], and different parts of Ethiopia [4,5,[18][19][20][21][22][23][24]. However, there is paucity of information on the prevalence of camel mastitis and its risk factors in Gomole district of Borena zone, Southern Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Mastitis is among the most important diseases of camels and has a worldwide distribution [5]. The disease can be either clinical or subclinical [6][7][8] and is associated with significant economic losses. These losses are attributed to the cost of treatment, reduced milk production, compromised quality of milk and public health concerns due to the widespread use of antimicrobials [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have shown that udder infections in lactating camels are widespread. In Africa, mastitis in camels has been reported in Egypt [ 6 , 14 ]; Somalia [ 8 ]; Ethiopia [ 7 , 15 ]; and Kenya [ 5 , 16 , 17 ]. The reported prevalence of camel mastitis under pastoralism in Kenya ranges from 46 to 93.3% [ 5 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%